2017
DOI: 10.1177/1474515117701060
|View full text |Cite
|
Sign up to set email alerts
|

Quality of chest compressions by healthcare professionals using real-time audiovisual feedback during in-hospital cardiopulmonary resuscitation

Abstract: Chest compression quality was poor according to the feedback system. However, the distribution of compression depth with regard to underlay points towards overestimation of depth when treating patients on a mattress. Audiovisual feedback devices ought to be further developed. Healthcare professionals need to be aware of the strengths and weaknesses of their devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…These results differ from a recent study using audiovisual feedback to assess compression rate and depth, where the most common problem was excessive compression depth. 23 However, the vast majority of these events occurred with the patient being treated on a mattress, whereas in the present study, CPR was performed on the floor. Results may therefore not be comparable.…”
Section: Chest Compressionsmentioning
confidence: 75%
“…These results differ from a recent study using audiovisual feedback to assess compression rate and depth, where the most common problem was excessive compression depth. 23 However, the vast majority of these events occurred with the patient being treated on a mattress, whereas in the present study, CPR was performed on the floor. Results may therefore not be comparable.…”
Section: Chest Compressionsmentioning
confidence: 75%
“…3,4,[9][10][11][12][13][14][15][16] Semark et al evaluated the quality of chest compressions in in-hospital cardiac arrest and found poor compression quality in 96% of the cases when frequency and depth were analyzed. 14 Abella et al also studied the quality of in-hospital CPR and found similar data to our findings, showing that the quality of multiple parameters was inconsistent and often did not meet the recommendations of published guidelines, even when performed by well-trained professionals. 16 Sutton et al analyzed the quality of in-hospital pediatric CPR, showing that the compressions were shallow in 27.2% of the cases, used excessive residual leaning force in 23.4%, and had an inadequate rate in 43.1%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies had found that the compression rates were generally too slow 9 . However, our study showed an opposite result, in that excessive compression rates were commonly observed.…”
Section: Discussionmentioning
confidence: 97%